Some apories regarding knowledge of time in Aristotle - Puente, Fernando Rey (2015)
The purpose of this paper is to uncover some difficulties in Aristotle's so-called Treatise on Time (chapters ten to fourteen of the fourth book of his Physics) and to point to some of the huge difficulties that arise with respect to the knowledge of time and to the aporias that underlie the Stagirite’s questions and answers on the subject. These aporias, it must be made clear, are related to his often uncertain and shifting use of cognitive, perceptive and intellective words; the problem, however, goes beyond terminology.